Exercise as a strategy to prevent APOEε4‐dependent phenotypes: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Foley, Kate E.; Diemler, Cory; Garceau, Dylan; Moore, Annah M.; Hohman, Timothy J.; Sasner, Michael; Howell, Gareth
Abstract: Background: Human data suggest cerebrovascular dysfunction precedes and exacerbates Alzheimer's disease (AD). APOE ε4 contributes to cerebrovascular decline with age, and APOE status interacts with angiogenesis pathways including the VEGF family to modify cognitive decline. However, the precise nature of this relationship is not known. Research suggests that running provides substantial health benefits that reduce risk for AD. Previous data from our lab showed that, transcriptionally, cerebrovascular processes such as vascular remodeling and angiogenesis terms can be altered short term running in young mice. Here, we are combining human and mouse studies to (i) understand the relationship between APOE status and the VEGF pathway in AD, and (ii) determine whether the effects of exercise on the cerebrovasculature are modified by APOE status. Method: To assess cerebrovascular health, we took several approaches: (i) transcriptional profiling, (ii) immunofluorescence of basement membrane, and (iii) immunofluorescence of leakage (fibrin). To assess exercise and metabolic differences, B6.APOE ε4/ε4 (risk) and B6.APOE ε3/ε3 (neutral) mice were run from 1‐4 months (mo) and 1‐12mos, as well as metabolic phenotyping including circulating plasma lipid levels, food intake, water loss, running speed, and gas exchange. Heterozygous B6.APOE ε3/ε4 mice are included to evaluate the potential hypomorphic/ hypermorphic function of the APOE ε4 allele on cerebrovascular health. Human data from ROSMAP and ADNI cohorts is being compared to mouse data. Result: Cerebrovascular dysfunction was evaluated in 2mo and 12mo B6.APOE ε3/ε3 and APOE ε4/ ε4 mice for basement membrane coverage and fibrin leakage which revealed an increase in COL4 and increased leakage, in 12mo female APOE ε4 / ε3 compared to B6.APOE ε3/ε3 mice. Analysis of 1‐4mo running data showed no transcriptional evidence that the cerebrovasculature was altered in young APOE ε4 or APOE ε3 carriers, suggesting longer term interventions are necessary. Human data shows patients that suffer a more severe cognitive decline have increasing levels of angiogenesis markers in the brain and blood. Our ongoing work aims to identify the mechanism between APOE ε4 and angiogenesis/cerebrovascular integrity. Conclusion: Recreated APOE ε4 mice recapitulate age‐dependent cerebrovascular deficits however running at a young timepoint will likely not affect cerebrovascular health. Longer term studies are underway to determine whether chronic running mitigates age‐dependent effects of APOE ε4 .